Evolution of an obstetrics and gynecology interprofessional simulation-based education session for medical and nursing students. Issue 43 (23rd October 2020) - Ogunyemi, Dotun; Haltigin, Christopher; Vallie, Stephanie; Ferrari, Thomas M.
Abstract : Abstract: Simulation and Objective Structured Clinical Examination assessment of learners can teach clinical skills proficiency in a safe environment without risk to patients. Interprofessional simulation-based education (IPSE) contributes to a transformation in students' understanding of teamwork and professional roles. Long term outcomes for stimulation and IPSE sessions, are less well studied. We hypothesized that a progressive interprofessional education simulation program incorporating both faculty and interprofessional student collaboration would improve medical students' knowledge retention, comfort with procedural skills, positive teamwork and respectful interaction between students. An Obstetrics and Gynecology IPSE for medical and nursing students (NS) was developed in collaboration between a school of medicine and a school of nursing from 2014 to 2017. By 2017, content included fetal heart rate case-based workshop; simulated vaginal delivery; cervical examination and assessment; contraception station including intrauterine device insertion practice; obstetric procedures including hands-on B-Lynch Suture practice. From 2014 to 2016, medical students completed attitude, knowledge, and perception surveys both pre and immediately post simulation, at 4 months, and 8 months. In 2017; all students completed self-assessments and received faculty-assessments. The program trained 443 medical and 136 NS. Medical students' knowledge, comfort, and interest increased significantly post simulation. Outcome scores decreased but were still significantly improved at 4 months but nearly dissipated by 8 months. There were no significant differences between medical and NS self-assessment or faculty-assessment scores regarding IUD insertion, cervical examination, or contraception quiz scores. Medical students' birth simulation self-assessment versus faculty-assessment scores were 8.6 vs 8.9, P < .001. Simulation improved students' short-term medical knowledge, comfort, and perception with some long-term persistence at 4–8 months. Medical and NS learned obstetrics and gynecology skills in a collaborative environment and in role-specific situations. Medical students had the opportunity to learn from NS. Positive teamwork and respectful interaction occurred between the students. Abstract : Supplemental Digital Content is available in the text